Learning from Power Sector Reform Experiences : The Case of Vietnam - Lee, Alan David (World Bank, Washington, DC, 2020)
Vietnam's power sector has developed rapidly since the 1990s to become a top performer among developing countries. This success has occurred mostly under a state-owned utility, Electricity Vietnam. Select market-oriented reforms to date have also had some positive impact. By the late 1990s, the Government realized the need to gradually introduce competition to ensure long-term sustainability without jeopardizing security of supply for the fast-growing economy. Vietnam's 2004 Electricity Law has provided the framework to develop a competitive power market, unbundle Electricity Vietnam, set prices that better reflect costs, promote private investment, and establish a regulatory authority. Today, state-owned entities continue to dominate the sector. Whereas the power market is partially competitive, improved operational efficiency and financial performance of generators in this market has contributed to keeping generation costs relatively low. Plans are broadly on track for further extensive reforms, including a clean energy transition. Lessons include that state-centric institutions can develop the power sector with top-level government commitment, highly-qualified staff, and consensus among sector institutions. Gradual reforms offer an opportunity to learn by doing; yet, the sequence of reforms matters. Introducing market mechanisms ahead of other elements may limit the market effectiveness and even make subsequent reform steps more difficult.